Analysis Indonesian Sharia Banks' Readiness to Face the Evolution of Financial Technology-Based Sharia Financial Services in Indonesia - Harfian, Muhammad Juang; Amalia, Euis; Terminanto, Ade Ananto; Rizal, Sofyan; Aziz, Roikhan Mochamad; Febriansyah, Febriansyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
The purpose of this study is to assess the level of readiness and steps taken by Bank Syariah Indonesia (BSI) in responding to the development of Financial Technology-based financial services. The research method used is descriptive qualitative by collecting data through observation, interviews, and documentation. The results of the study indicate that Bank Syariah Indonesia (BSI) has prepared itself by considering the Slameto concept, which includes aspects of readiness to meet demands and goal motivation as well as physical, mental, and emotional balance. In addition, the study also discusses efforts in building technology to improve employee skills and knowledge, especially in the areas of security, risk, and fraud, which have been achieved through Core System Modernization, Connectivity and Infrastructure, Monitoring and Management of Combined Data, Structure, Business Mentoring, and Internal Improvement, as well as through Unifled Platform & Customer 360 and Digital Expansion & Open Banking. All of this aims to improve employee quality through training to adapt to the digital era, develop human resources, improve security and infrastructure, and expand Bank Syariah Indonesia's (BSI) digital network.